1999
DOI: 10.1139/b99-109
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of ectomycorrhiza communities from three conifer species planted on forest gap edges

Abstract: We examined the ectomycorrhiza communities on lodgepole pine (Pinus contorta var. latifolia Engelm), white spruce (Picea glauca (Moench) Voss), and subalpine fir (Abies lasiocarpa (Hook.) Nutt) seedlings planted together on mature-forest edges in northwestern British Columbia. We examined 32 seedlings of each tree species, grouped by pairs along the north and south edges of eight gaps. We found 74 morphotypes in total, with an average of 52 morphotypes per tree species. Morphotypes with emanating hyphae or str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 15 publications
(7 reference statements)
1
31
0
Order By: Relevance
“…On the whole, the difference of the vegetation type was more effective on fruiting and species composition of LP than on those of EP. This result suggests that, in LP species, there exists a sort of "host preference" in the sense of Imazeki and Hongo (1987) and Otani and Hongo (1988), who based their reports on fruit body collecting experiences in various types of forests, rather than "host specificity" in the sense of Molina and Trappe (1982), Kranabetter et al (1999), and Massicotte et al (1999), who based their reports on observation of ECM connection between fungi and their host plants.…”
Section: Characteristics Of Fruiting By the Urea Treatmentmentioning
confidence: 98%
See 1 more Smart Citation
“…On the whole, the difference of the vegetation type was more effective on fruiting and species composition of LP than on those of EP. This result suggests that, in LP species, there exists a sort of "host preference" in the sense of Imazeki and Hongo (1987) and Otani and Hongo (1988), who based their reports on fruit body collecting experiences in various types of forests, rather than "host specificity" in the sense of Molina and Trappe (1982), Kranabetter et al (1999), and Massicotte et al (1999), who based their reports on observation of ECM connection between fungi and their host plants.…”
Section: Characteristics Of Fruiting By the Urea Treatmentmentioning
confidence: 98%
“…First, the quantity and size of fruit bodies are known to be generally larger in ECM species than in SAP ones (Fukiharu 1991;Fukiharu and Kato 1997;Murakami 1987;Vogt et al 1992). Second, the existence of host specificity or host preference as mentioned by Imazeki and Hongo (1987), Otani and Hongo (1988), Kranabetter et al (1999), Massicotte et al (1999), and Molina and Trappe (1982) may affect the species composition of ECM communities. Because these two characteristics are quite widespread, they may also be observed in fruiting of the ammonia fungi.…”
mentioning
confidence: 99%
“…Most studies focused on effects of disturbance on residual fungus inoculum and on the amount and diversity of ectomycorrhiza (EM) types on seedlings planted in situ or in greenhouse experiments Parke et al, 1983bParke et al, , 1984Pilz and Perry, 1984;Dahlberg and Stenström, 1991;Harvey et al, 1996;Jones et al, 1997Jones et al, , 2002. Some studies have also examined EM diversity on seedlings planted near forest edges or aggregates of retained live trees (Kranabetter and Wylie, 1998;Kranabetter, 1999;Kranabetter et al, 1999;Kranabetter and Friesen, 2002). A universal finding emerges from this work: the EMF community as seen on root tips changes significantly in disturbed sites compared to undisturbed, nearby forests (Jones et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Dynamics of fruit-body production and mycorrhiza formation of ectomycorrhizal ammonia fungi in warm temperate forests in Japan Dighton et al 1986;Arnolds 1988;Vogt et al 1992;Keizer and Arnolds 1994;Jumpponen et al 1999;Walker and Miller 2002) and then attempted to identify ectomycorrhizae in terms of fungal symbionts by morphological typing (Danielson and Pruden 1989;Baxter et al 1999;Kranabetter et al 1999;Massicotte et al 1999) and by polymerase chain reaction-restriction enzyme fragment length polymorphism (PCR-RFLP) analysis (Gardes et al 1991;Bruns 1993, 1996;Dahlberg et al 1997;Gehring et al 1998;Jonsson L. et al 1999;Jonsson T. et al 1999;Jonsson L. et al 2000;Glen et al 2001;Peter et al 2001). Studies on changes in the fungal fl ora after Napplication (N-fertilization) have also been conducted (Alexander and Fairley 1983;Termorshuizen 1993;Boxman et al 1998;Brandrud and Timmermann 1998;Jonsson et al 2000;Peter et al 2001) and revealed the effects of air pollution and acid rain containing NO x on fungi in Europe.…”
Section: Akio Imamura · Takakazu Yumotomentioning
confidence: 99%
“…
Walker and Miller 2002) and then attempted to identify ectomycorrhizae in terms of fungal symbionts by morphological typing (Danielson and Pruden 1989;Baxter et al 1999;Kranabetter et al 1999;Massicotte et al 1999) and by polymerase chain reaction-restriction enzyme fragment length polymorphism (PCR-RFLP) analysis (Gardes et al
…”
mentioning
confidence: 99%